Dampak Kampanye Propaganda Digital AS terhadap Persepsi Publik Studi Kasus : Konflik Suriah Tahun 2020-2024 - Diva Rachel Aurelia; Fiori Amelia Putri; Jasmine Benida Putri Baenuri; Nadia Kamilatul Azizah; Ruben Ezra Nathaniel (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
In the increasingly developing digital era, social media and digital platforms have become effective tools for disseminating information, including political propaganda. In the context of prolonged war and geopolitical complexity, digital propaganda has become an important tool in shaping public opinion and influencing people's perceptions of the actors involved in the conflict. Using a qualitative approach, this research analyzes social media content, online news, and other digital platforms to identify key themes in the narrative conveyed by the US government and their impact on domestic and international public perceptions. The research results show that the US digital propaganda campaign not only serves to support the country's foreign policy, but also to build a positive image of military intervention and support for opposition groups in Syria. This research found that there was a significant shift in public perception triggered by information spread through social media, where many users were exposed to narratives that tended to support US interests. Thus, this study highlights the importance of understanding the role of digital media in modern conflicts and its implications for foreign policy and social dynamics.